PENGARUH KUALITAS PELAYANAN DAN HARGA TERHADAP LOYALITAS KONSUMEN PREANGER RESTORAN DI GRAND HOTEL PREANGER BANDUNG - Dessy Sagita, - (2009)
Purpose this research is to know about : effect of service quality and selling price to customers loyalty at Preanger Restaurant Grand Hotel Preanger Bandung . Method which use in this research is analytic description method with systematic nonrandom sampling and incidental sampling technique. 100 customers at Grand Preanger Restaurant are become sample. I use double regression linier for data analysis in this research. Research show that the effect of service quality and selling price to customers loyalty is 96,2% , otherwise the rest influence by other factors. Price variable have bigger effect than service quality variable, which are 55,8% for price and 41,5% for service quality. Prefer to all explanation above it is certainly need to held a training class,/ refreshment training for all employee off F&B Department specially restaurant staff, so all of staff become more aware to guest needs and satisfaction. We trained staff will give service fluently according to the standard operation of service. Beside the customers the advantage from training class it self. To keep the customers more loyal, it certainly needs some programs, such as : member heritage club, gathering, and other promote from F&B Department, specially restaurant to keep the customers more loyal and also satisfy. As along as all staff keep up the service quality that will effect to the price and also the customers will take the advantage and the company also will get the advantage both from customers loyalty and the money they spent.